2020
DOI: 10.4314/tjpr.v19i9.9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of neo-lignan isoamericanin A via suppression of NF-κB in liposaccharide-stimulated RAW 264.7 cells

Abstract: Purpose: To investigate the potential anti-inflammatory effects of the seeds of Opuntina humifusa and its active constituents.Methods: The extract of O. humifusa seeds was tested for the inhibition of nitric oxide (NO) production in liposaccharide (LPS)-stimulated RAW 264.7 cells using Griess reagent. The active constituents were isolated using bioassay-guided isolation methods. The effects of the active constituent on NO, proinflammatory cytokines, nuclear factor-kappa B (NF-κB) and nuclear factor of kappa li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Thus, the inactivation of NADPH oxidase helps suppress neuroinflammation. Our data showed that the inflammation inhibition effect of ISOA was obtained by reducing NF‐κB signaling pathway, evidenced by lowed IκBα phosphorylation and NF‐κB p65 nuclear translocation, which is consistent with the previous report (Ji et al, 2020). Moreover, we observed, for the first time, that ISOA suppressed NF‐κB p65 phosphorylation and IκBα degradation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, the inactivation of NADPH oxidase helps suppress neuroinflammation. Our data showed that the inflammation inhibition effect of ISOA was obtained by reducing NF‐κB signaling pathway, evidenced by lowed IκBα phosphorylation and NF‐κB p65 nuclear translocation, which is consistent with the previous report (Ji et al, 2020). Moreover, we observed, for the first time, that ISOA suppressed NF‐κB p65 phosphorylation and IκBα degradation.…”
Section: Discussionsupporting
confidence: 93%
“…Airy Shaw (Euphorbiaceae) (Chen et al, 2020). Previous studies reported ISOA could act as a prostaglandin I2 inducer (Ji et al, 2020) and possesses pharmacological properties against oxidative stress (Suzuki et al, 2016) and inflammation (Chen et al, 2020; Ji et al, 2020). Therefore, it is reasonable to assume that ISOA possesses the potential to treat AD.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Cho et al [ 78 ] reported that chloroform and ethyl acetate fractions of O. humifusa cladodes were able to decrease NO production in LPS-stimulated RAW 264.7 macrophages, pointing to quercetin as one of the main compounds responsible for this behavior. Moreover, they also noticed that both fractions differently modulated cytokines’ gene expression, especially for iNOS, IL-6, and IL-1β, suggesting the implication of other bioactive components from the species in the anti-inflammatory potential, while Yeo et al [ 91 ] showed that methanolic extracts obtained from the seeds of the same species reduced NO production from LPS-stimulated macrophages’ RAW 264.7. The isolated compound americanin A was found to be responsible for reducing iNOS and pro-inflammatory cytokines’ (TNF-α and IL-6) expression levels, which resulted principally by preventing NF-κB translocation into the nucleus.…”
Section: Opuntia Sp In Inflammationmentioning
confidence: 99%